Il Codex Purpureus Rossanensis: status quaestionis e problemi aperti - Maniaci, Marilena; Orsini, Pasquale (Scrineum, 2018)
Ever since its rediscovery in 1831 and the first report issued on it in 1846, the CodexpurpureusRossanensishas attracted the attention of scholars, chiefly on account of its decorative and textual characteristics. Far less commonplace are studies specifically dedicated to the analysis of the codex’s material and graphic aspects. The present contribution stems from the opportunity―generously provided to the authors―to study the original codex, and also from a desire to closely re-examine its codicological and palaegraphical features, with the aim of producing an updated statusquaestionisenhanced with some new critical insights.